2018
DOI: 10.1038/s41598-017-18490-9
|View full text |Cite
|
Sign up to set email alerts
|

Engineered mesenchymal stem-cell-sheets patches prevents postoperative pancreatic leakage in a rat model

Abstract: Post-operative pancreatic fistula (POPF) following pancreatic resection is a life-threatening surgical complication. Cell sheets were prepared and harvested using temperature-responsive culture dishes and transplanted as patches to seal POPF. Two different mesenchymal stem cell (MSC) sheets were compared in terms of the preventative ability for pancreatic leakage in a rat model. Both rat adipose-derived stem cell (rADSC) and bone marrow-derived stem cell (rBMSC) sheets were transplanted. Those rADSC and rBMSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…The Endothelial Progenitor Cells (EPC) treatment strategy take advantages of preserving or regenerating tissue to develop towards clinical application [1][2][3]. However, the disadvantage of single cells transplantation related aggregation and necrosis make the the feasibility and effectiveness of the approach remain insu cient and di cult in clinical trials [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The Endothelial Progenitor Cells (EPC) treatment strategy take advantages of preserving or regenerating tissue to develop towards clinical application [1][2][3]. However, the disadvantage of single cells transplantation related aggregation and necrosis make the the feasibility and effectiveness of the approach remain insu cient and di cult in clinical trials [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Previously described cell-assembled systems for different tissues and organs may therefore take advantage of the use of our approach to accelerate the time required for ex vivo culture 33 39 . In a simple setting, our technology can be combined with the use of temperature-responsive plates, allowing the detachment of cell sheets by a temperature switch as already tested for macromolecular “crowders” 36 , 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Over 15 years of clinical data support enhanced therapeutic properties for autologous‐sourced cell sheets through increased cell retention at target tissues (Ebihara et al, 2012; Iwata et al, 2018; Kanzaki, Takagi, Washio, Kokubo, & Yamato, 2017; Nishida et al, 2004; Ohki et al, 2012; Sawa et al, 2015; Yamaguchi et al, 2017; Yamamoto et al, 2017). Recently, several preclinical studies have also reported MSC sheet use in wound healing, heart, and pancreas regeneration (Kato et al, 2015; Kim et al, 2018; Miyahara et al, 2006). However, for reliable clinical performance and regulatory acceptance, standardized MSC sheet fabrication methods yielding reproducible cell‐based products with quality control specifications must first be developed.…”
Section: Introductionmentioning
confidence: 99%